Experimental study on effects of combustion atmosphere and coal char on NO2 reduction under oxy-fuel condition. Issue 4 (August 2019) - Wang, Chang'an; Wang, Pengqian; Du, Yongbo; Che, Defu
Abstract: Nitrogen oxides (NO x ) as the principal air pollutants are mainly from the combustion of fossil fuels. Oxy-fuel combustion is a promising clean coal technology, by which carbon dioxide (CO2 ) can be captured in large-scale and NO x emission can be reduced significantly. The formation of nitrogen dioxide (NO2 ) in oxy-fuel combustion exceeds that under traditional air condition. However, the specific studies on NO2 chemistry under oxy-fuel condition are still insufficient and the functional mechanisms of minerals and combustion atmosphere on NO2 reduction have yet to be fully understood. The objective of present study is to experimentally clarify the effects of combustion atmosphere and coal char on NO2 reduction in oxy-fuel combustion using a fixed-bed reactor. Experimental results showed that the decomposition of NO2 had a strong temperature dependence and the NO2 reduction rate showed a positive variation with temperature. The strength of catalytic activity in NO2 reduction to nitric oxide (NO) was Fe2 O3 > MgO > CaO > Al2 O3 > Na2 CO3 > K2 CO3 > SiO2 . In addition, the increased concentrations of carbon monoxide (CO) and CO2 could promote the reduction of NO2, while the low content of CO2 only established a slight impact on NO2 reduction. However, the increase of oxygen (O2 ) concentration displayed an inhibition effect on NO2 reduction to a certain extent. The variation of atmosphere in oxy-fuel combustion generated a substantial influence on the creation and reduction of NO2 . The char prepared in lower temperature exhibited a higher promotion effect on the consumption of NO2 . Higher contents of fixed carbon and basic oxides had more obvious stimulation effects on NO2 reduction. Fixed carbon had a superior activity in NO2 reduction than ash. The kinetic analysis indicated that high content of CO and the presence of char could reduce the apparent activation energy of NO2 reduction. The present study can be helpful to improve the understanding of NO2 chemistry in oxy-fuel combustion. Highlights: Effects of combustion atmosphere and coal char on NO2 reduction were studied. The decomposition of NO2 was largely temperature-dependent. The increased concentrations of CO and CO2 could promote the reduction of NO2 . Fixed carbon and basic oxides had significant stimulation effects on NO2 reduction. Fixed carbon presented a superior activity in NO2 reduction than ash.